Pengembangan Model Promosi Media Sosial Untuk Peningkatan Penjualan Usaha Mikro “Nasi Jinggo” di Kota Denpasar - Ni Nyoman Kerti Yasa; I Gusti Ayu Ketut Giantari; Henny Rahyuda; Ni Wayan Ekawati; Putu Dyah Krismawintari (Forum Kerjasama Pendidikan Tinggi, 2021)
The COVID-19 pandemic has had a negative impact on many businesses, including the “Nasi Jinggo” micro business in Denpasar City, especially the Nasi Jinggo angkringan located on Jalan Gajah Mada, Denpasar. The amount of sales that can be achieved, the operating profit that can be earned, and the number of customers that can be served have decreased. Therefore, it is necessary to consider alternatives that can be employed to address existing issues. One approach to do this is to create a promotional model that integrates several relevant social media platforms. The purpose of this community service is to develop Nasi Jinggo's entrepreneurs' abilities to promote social media and create social media promotion media such WhatsApp, Instagram, and Facebook to communicate their products. This service includes training on the importance of social media promotion and also guidance or consultation on how to make social media promotions through WhatsApp. This project takes place on Jalan Gajah Mada, Denpasar City, which is a member of the micro business group or Angkringan Nasi Jinggo. After the activity was carried out, the Nasi Jinggo micro business owner who had agreed to use the business name